THE RESEARCH AGENDA OF BRAZILIAN SOCIOLOGY AT THE BEGINNING OF THE MILLENNIUM - Luiz Augusto Campos; Marcelo Augusto de Paiva dos Santos; Mayra Juruá; Candido, Marcia. (Cadernos de Pesquisa, 2023)
Many works have sought to define the research agenda of Brazilian sociology, its temporal evolution, and other internal and external dynamics. However, the methods employed in the thematic classification of the discipline are still rudimentary. To address this issue, this article applied text processing techniques, particularly Topic Modeling, to analyze over 3 thousand doctoral theses published at the beginning of the millennium. The results indicate that our “new” sociology is characterized by a relative decline in the importance of traditional themes, such as studies on labor, in favor of more diverse topics, such as violence and gender. These transformations seem to reflect guidelines from funding agencies and changes in public debate, posing new challenges on the horizon of the discipline.